A peek into cancer-associated fibroblasts: origins, functions and translational impact - Valerie S. LeBleu; Raghu Kalluri (The Company of Biologists, 2018)
In malignant tumors, cancer cells adapt to grow within their host tissue. As a cancer progresses, an accompanying host stromal response evolves within and around the nascent tumor. Among the host stromal constituents associated with the tumor are cancer-associated fibroblasts, a highly abundant and heterogeneous population of cells of mesenchymal lineage. Although it is known that fibroblasts are present from the tumor's inception to the end-stage metastatic spread, their precise functional role in cancer is not fully understood. It has been suggested that cancer-associated fibroblasts play a key role in modulating the behavior of cancer cells, in part by promoting tumor growth, but evolving data also argue for their antitumor actions. Taken together, this suggests a putative bimodal function for cancer-associated fibroblasts in oncogenesis. As illustrated in this Review and its accompanying poster, cancer-associated fibroblasts are a dynamic component of the tumor microenvironment that orchestrates the interplay between the cancer cells and the host stromal response. Understanding the complexity of the relationship between cancer cells and cancer-associated fibroblasts could offer insights into the regulation of tumor progression and control of cancer.